2014
DOI: 10.1016/j.niox.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Kefir administration reduced progression of renal injury in STZ-diabetic rats by lowering oxidative stress

Abstract: This study aimed at assessing the effects of Kefir, a probiotic fermented milk, on oxidative stress in diabetic animals. The induction of diabetes was achieved in adult male Wistar rats using streptozotocin (STZ). The animals were distributed into four groups as follows: control (CTL); control Kefir (CTLK); diabetic (DM) and diabetic Kefir (DMK). Starting on the 5th day of diabetes, Kefir was administered by daily gavage at a dose of 1.8 mL/day for 8 weeks. Before and after Kefir treatment, the rats were place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 40 publications
4
32
0
3
Order By: Relevance
“…These results were recently confirmed in an experimental model of MS [116]. In agreement with this study's results, Punaro et al [117] also demonstrated antioxidative and renoprotective effects after kefir supplementation using STZ-diabetic rats. Ostadrahimi et al [118] showed that kefir reduces glycemia and HbA1c in type 2 diabetes patients, suggesting that this symbiotic therapy may be an interesting adjuvant in the treatment of diabetes.…”
Section: Benefits Of Kefir On Metabolic Syndrome: Focusing On Insulinsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were recently confirmed in an experimental model of MS [116]. In agreement with this study's results, Punaro et al [117] also demonstrated antioxidative and renoprotective effects after kefir supplementation using STZ-diabetic rats. Ostadrahimi et al [118] showed that kefir reduces glycemia and HbA1c in type 2 diabetes patients, suggesting that this symbiotic therapy may be an interesting adjuvant in the treatment of diabetes.…”
Section: Benefits Of Kefir On Metabolic Syndrome: Focusing On Insulinsupporting
confidence: 91%
“…Ostadrahimi et al [118] showed that kefir reduces glycemia and HbA1c in type 2 diabetes patients, suggesting that this symbiotic therapy may be an interesting adjuvant in the treatment of diabetes. Other authors have shown that kefir was able to reduce ROS intracellular levels in insulinresponsive muscle cells [117] and in STZinduced diabetes mellitus in rats [118]. In addition, proteinuria and azotemia observed in rats with type I diabetes mellitus were reduced by treatment with kefir, an effect apparently related to its antioxidant capacity [115].…”
Section: Benefits Of Kefir On Metabolic Syndrome: Focusing On Insulinmentioning
confidence: 95%
“…Also, several animal studies have observed positive effects of probiotic administration [101,102,103,104] which can have a consequential positive effect on public health of humans by lowering antibiotic consumption for animals used in food production. This will consequently lower the presence of drugs and multi-resistant organisms in the environment (including drinking water).…”
Section: Resultsmentioning
confidence: 99%
“…In STZ-induced DM, it has been shown that daily administration of kefir caused an improvement in the increased levels of glycemia and glucose tolerance compared to conventional fermented milk [168,178,179]. Interestingly, kefiran, which is an exopolysaccharide isolated from kefir grains, has been shown to decrease blood pressure and blood glucose in animal models of hypertension [180] and an animal model of intolerance to glucose overload [181].…”
Section: Beneficial Effects Of Probiotics: Highlights Of Treatmentmentioning
confidence: 99%